(untitled) (Revista Brasileira Multidisciplinar, 2011)
Aimed at financial inclusion of family farmers, solidary credit cooperatives act – besides mere access to credit – to improve the quality of life of those with whom they interact. Such as banks, credit cooperatives as financial institutions are subject to standards and regulations of the National Financial System, fact that generates a series of procedures and rules in order to guarantee their operation. In this sense, this paper emphasizes, through the speeches of their members, the dilemma in which we see one of these cooperatives: how to keep an alternative proposal to the commercial banks, without disobeying the rules and procedures dictated by the National Financial System? According to the data obtained in the 32 interviews and in the observation of directors’ meetings, during the elaboration of the Master research entitled "The Solidary Credit Cooperativism and Social Representations of Cooperation in the cities of Tombos and Araponga/MG", on the one hand, there is a preoccupation with guaranteeing that the financial system’s rules are followed and that the cooperatives have more professional management. On the other hand, there is a huge preoccupation with not to allow that these rules affect the differentiated performance form, in which farmers have access to financial services they need. There is not an immediate or definitive solution for this question. There are only some initial notes that do not guarantee results for all the aspects considered important, like the appreciation of the bonds of trust in consonance with the performance of a financial institution in expansion.